Pengaruh Financial Distress, Auditor Switching, Audit Report Lag, Leverage Dan Likuiditas Terhadap Opini Audit Going Concern - Yanti, Mahardini Syahputri (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study aims to examine the effect of financial distress, auditor switching, audit report lag, leverage and liquidity on going concern audit opinion in energy sector companies listed on the Indonesia Stock Exchange in 2019-2023. This study uses a data collection method in the form of financial reports (annual reports) of companies obtained through www.idx.co.id and the company's official website. The population in this study were all companies listed on the Indonesia Stock Exchange, totaling 938 companies. The sampling technique in this study used the purposive sampling method with a sample size that met the criteria of 60 companies in 5 years of observation, so that a sample size of 300 data was obtained. This study uses logistic regression analysis with the help of IBM SPSS 25. The results of the study indicate that financial distress, audit report lag, and liquidity have an effect on going concern audit opinions in energy sector companies listed on the Indonesia Stock Exchange. While auditor switching and leverage do not affect going concern audit opinions in energy sector companies listed on the Indonesia Stock Exchange.